Does inequality-adjusted human development reduce the impact of natural disasters? A gendered perspective - Roy Chowdhury, Joyita; Parida, Yashobanta; Agarwal Goel, Prarthna (World Development, 2021)
This paper examines how inequality-adjusted human development (IHD) helps minimize male and female flood fatalities across 19 Indian states between 1983 and 2013. We investigate if a higher achievement in the IHD index has affected male and female flood deaths differently while controlling for direct spending on disaster adaptation measures and socio-political factors. The empirical results suggest that Indian states with better IHDI score experience lower flood fatalities in aggregate. A 10% increase in IHDI at the sample mean results in the probability of 38 fewer total deaths from floods. Furthermore, we find a gender-differentiated impact of disasters as males suffer fewer flood fatalities than females with a rise in IHDI. The findings suggest that an additional 10% increase in IHDI at the sample mean results in the probability of 26 fewer male deaths from floods, and the same 10% rise in IHDI shows the probability of 12 fewer female deaths due to floods. Women’s involvement in social, political, and economic decision-making measured through women’s participation in voting in elections, grant them access to flood mitigation and aversion measures, which can reduce the impact of a disaster. However, the current participation rate is not adequate to reduce female flood mortality substantially. Women’s socially constructed responsibilities impose constraints on their participation in activities outside the household, including their mobility to the non-agricultural sector, and therefore, reduce access to warning information, which can increase vulnerability to disasters.
Keywords: Gender budgeting; Gender-wise flood fatalities; Human development; Negative binomial estimate; Women’s participation in electoral process; _z:class:countries